Synthesis and Characterization of Magnetically Separable Porous Titanium Silicate Nanocomposite Catalyst for Environmental Applications. (2017) - Kumar, A.A.; Rajini, A.; Venkatathri, N.
Abstract: Herein we developed magnetically separable porous Titaniumsilicate-Fe3 O4 (TSFO) hybrid photocalatalyst. The synthesized porous TSFO were well characterized by various analytical techniques like XRD, FE SEM, FTIR and UV-DRS for structural and chemical properties evaluation. FESEM results shows the growth of finely distributed Fe3 O4 particles in the titanium silicate matrix. Porous TSFO has a great influence on the electronic and optical properties. The material was found to combine the advantages of high photocatalytic activity towards degradation of methylene blue under UV light irradiation.